High-performance communication networks, second edition - Walrand, Jean.; Varaiya, Pravin ([S.l.] : Morgan Kaufmann, 1999)
By focusing on the convergence of the telephone, computer networking, cable TV, and wireless industries, this fully revised second edition explains current and emerging networking technologies. The authors proceed from fundamental principles to develop a comprehensive understanding of network architectures, protocols, control, performance, and economics. Communications engineers, computer scientists, and network administrators and managers will appreciate the book for its perspectives on the innovations that impact their work. Students will be enriched by the descriptive and thorough coverage of networking, giving them the knowledge to explore rewarding career opportunities. * Provides the most recent information on * wide and local area networks, including WDM and optical networks, Fast and Gigabit Ethernets * access networks, such as cable modems and DSL; * approaches for quality-differentiated services in IP and ATM networks. * Examines the Internet, including proposed advances for improved performance and quality of service. * Presents a comprehensive discussion of wireless networks for voice and data. * Explains the economic factors and technical tradeoffs that guide network development. * Derives (in self-contained sections) the most important mathematical results of network performance.